Unoperated complete unilateral cleft lip and palate: A case report on occlusion, craniofacial morphology and oral function - Sakuda, Mamoru; Maeda, Sachiko; Kakiuchi, Yasuhiro; Kitamura, Takashi; Nakagawa, Koichi; Horisaka, Takashi; Yasuda, Yoshihide; Yoshida, Kenmi; Wada, Takeshi; Shimada, Junji; Sugimura, Masahito; Tsuchiya, Masafumi; et al. (Journal of Japanese Cleft Palate Association, 1983)
A 26-year old female with unoperated complete unilateral cleft lip and palate was reported. 1. Occlusion: No cross-bite was observed in both the anterior and buccal segments. 2. Craniofacial morphology: Analysis of the lateral roentogenographic cephalograms revealed that the length of the anterior cranial base was in the normal range, the maxilla was loca t e d anteriorly relative to the anterior cranial base and the maxillary depth was larger than th e noncleft subjects, although its vertical growth was less. Form and position of the mandible were in the category of the non-cleft subjects. These findings suggest that restricted growth, especially in the anteroposterior direction, of both jaws observed in the operated UCLP patients w a s caused by the plastic surgery during the infantile and early preschool period. 3. Speech: Severe hypernasality was evident. 4. Facial appearance: Analysis of Moir e topography indicated the deviation of tip of the nose to the non-cleft side. 5. Function of the tongue during swallowing: Since the lip, alveolus and palate were kept wide open, the usual stripping action of the tongue was not observed but peculiar movement of the tongue was evident. That is, according to the cine-radiography, dorsum of the tongue w as elevated to seal the cleft and food was kept on the floor of the mouth at the first phase of swallowing. Food was, then, swallowed along the lateral margin of the tongue. According t o the EMG activity of the tongue during swallowing, extremely long period of time was necessary for an act of swallowing in comparison to the non-cleft subjects. The pattern of the EMG activity was found to be polyphasic which was not common in the non-cleft subjects.